(untitled) (Superficies y Vacío, 2012)
Development and use of food packaging based on biomaterials have gained significant interest due to the need to reduce and replace the use of plastics and synthetic packaging for eco-friendly materials. In addition, these materials can act as semipermeable barriers while preserving the organoleptic characteristics of plant products. In the present work, gelatin-carboxymethylcellulose based edible films were prepared studying the effects of glycerol content and pH on their physicochemical properties. Also, the effect of the films on the postharvest shelf-life of guava fruit was determined. The characterization of the films was performed through the puncture strength test, water vapor diffusion coefficient and water solubility. Results indicated that both, glycerol and pH were determinant on the evaluated properties. Fruits coated with edible films showed lower weight losses and lower firmness losses as compared to control fruits, however, no differences were found in °Brix.